IoT-Based Medical Health Monitoring System with a Web Interface - Cantika Tri Inayah; Ade Silvia Handayani; Nasron Nasron (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
Health technology is increasingly developing along with the development of information and communication technology, where these advances are used to improve the quality of health services, especially in remote patient monitoring through telemedicine, M-Health and Telehealth. The development of the times has also brought telemedicine to a wider realm through M-Health and Telehealth which uses digital technology and wireless communication to enable monitoring of patient conditions, besides that websites are also used for wireless monitoring and data collection of patients because they have wide accessibility. This study aims to design a website that can integrate the data of the size of health sensor devices into an Internet of Things-based platform to display body temperature, blood oxygen, and ECG data in real-time. The test results show that all website features are running well, where the website runs well depending on the network used.